Straw Management Adoption Capacity in Long An Province - Ong Quoc Cuong; Vu Duong Quynh; Bui Tan Yen; Sander, Björn Ole; Vu Hong Trang; Barnard, Jennifer; Nguyen Van Hung; Nelson, Katherine (International Rice Research Institute, 2022)
The study aims to evaluate the straw management adoption capacity in Long An province. Key informant interview (KII) with district-level DARD officials in Long An province were conducted to determine the straw management adoption capacity in Winter-Spring, Summer-Autumn, and Autumn-Winter season.